Deterrence of financial misreporting when public and private enforcement strategically interact - Schantl, Stefan F.; Wagenhofer, Alfred (Journal of Accounting and Economics, 2020)
This paper studies strategic interactions between public and private enforcement of accounting regulation and their consequences for the deterrence of financial misreporting. We develop an economic model with a manager, a public enforcement agency, and an investor and derive equilibrium strategies for manipulative effort, routine investigative effort, and costly private litigation. Our main results are as follows. (i) Strengthening private enforcement unambiguously enhances deterrence, whereas strengthening public enforcement can exacerbate misreporting, due to a crowding out of private enforcement. We provide conditions under which (ii) the enforcer's investigation incentives first increase and then decrease in the strength of private enforcement, (iii) public and private enforcement are strategic substitutes, (iv) the number of enforcement actions is misleading about public enforcement effectiveness, and (v) strengthening private enforcement decreases litigation risk. We also discuss implications of our results for empirical research.